Graphene van der Waals heterostructures for high-performance photodetectors. Issue 36 (27th August 2019) - Geng, Huijuan; Yuan, Di; Yang, Zhi; Tang, Zhenjie; Zhang, Xiwei; Yang, Kui; Su, Yanjie
Abstract : We present a comprehensive review on the recent progress of graphene vdW heterostructure photodetectors and give further perspectives in this emerging field. Abstract : Graphene van der Waals (vdW) heterostructures with atomic level interfaces can be formed by stacking atomically layered semiconducting nanomaterials. Their photoelectric properties can not only be determined by graphene and semiconducting nanomaterials, but also dramatically tuned by the electron coupling interaction at the interface. By combining the high carrier mobility property of graphene with the excellent light absorption properties of semiconducting nanomaterials, graphene vdW heterostructures are considered as an excellent candidate for the development of next-generation optoelectronic nanodevices. In this review, we first introduce briefly the device fabrication and basic parameters of photodetectors based on graphene vdW heterostructures. Next, we present a comprehensive review on the recent progress of photodetectors based on different graphene vdW heterostructures obtained in the past few years, and the interlayer charge-transfer process is addressed as well. Finally, the current challenges are summarized and further perspectives are given for this emerging field.